Efficacy of PGF 2alpha , CIDR and Ovsynch treatment on estrus induction and fertility in postpartum buffaloes - A field study - SATHIAMOORTHY, T; PARTHASARATHY, R; KATIIIRCHELVAN, M (The Indian Journal of Animal Reproduction, 2023)
A total of forty five postpartum buffaloes were equally divided into group I, II and III. The group I animals were treated with PGF2alpha after palpation of corpus luteum. The group II animals were treated with CIDR and removed after 9 days. The group III animals were treated with GnRH analogue and 6 days later they were administered with PGF2alpha . A second injection of GnRH analogue was administered after 48 hours of PGF2alpha treatment. Percentage of induced estrus were 66.6%, 86.6% and 60.0% in group I, II and III, respectively. Mean onset of induced estrus were 54.4 ± 7 .6, 42.2 ± 6.6 and 47.4 ± 8.4 in group I, II and III, respectively. First service conception rate was 50.0%, 46.1 % and 66.6% in group I, II and III, respectively. From this it may be concluded that Ovsynch protocol is giving fertility rate upon fixed-time breeding in estrus synchronized buffaloes at field level.